The ovine HIAT1 gene: mRNA expression, InDel mutations, and growth trait associations - Luo, Yunyun; Akhatayeva, Zhanerke; Mao, Cui; Jiang, Fugui; Guo, Zhengang; Xu, Hongwei; Lan, Xianyong (Frontiers in Veterinary Science, 2023)
The hippocampal abundant transcript 1 (HIAT1) gene, also known as major facilitator superfamily domain-containing 14A (MFSD14A), encodes for a transmembrane transporter protein and has been previously shown to be correlated with milk production in buffalo and sheep breeds, as well as growth traits in chicken and goats. However, tissue level distribution of the ovine HIAT1 gene, as well as its effect on body morphometric traits in sheep, has yet to be studied. In this study, the HIAT1 mRNA expression profile of Lanzhou fat-tailed (LFT) sheep was determined. This data revealed that HIAT1 was widely expressed in all examined tissues, and was particularly abundant in the testis of male sheep. Additionally, a 9-bp insertion mutation (rs1089950828) located within the 5’-upstream region of HIAT1 was investigated in samples taken from 1498 sheep of three indigenous Chinese sheep breeds and included: Luxi black-headed (LXBH) sheep, Guiqian semi-fine wool (GSFW) sheep, and LFT sheep. The wildtype allele frequency ‘D’ was found to be more prevalent than that of the mutant allele ‘I’. Furthermore, low genetic diversity was confirmed in all sampled sheep populations. Subsequent association analyses indicated an association between the 9-bp InDel mutation of interest and the morphometric traits of LXBH and GSFW sheep. Furthermore, yearling ewes with a heterozygous genotype (ID) demonstrated smaller body sizes, while yearling rams and adult ewes with the heterozygous genotype were found to have overall better growth performance. These findings imply that functional InDel polymorphism (rs1089950828) has the potential to be utilized for marker-assisted selection (MAS) of growth traits in domestic Chinese sheep populations.